2018
DOI: 10.1111/jfpe.12831
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscopy study of microstructure damage and micromechanical behavior of potato tissue by impact during storage

Abstract: Impact damage of potato occurs during handling, transportation, sorting, and storage. In this research, scanning electron microscopy (SEM) analysis was employed to investigate the micromechanical changes of potato tissue by applying impact levels of 0 (control), 0.032, 0.185, and 0.335 J over a 16‐week storage period. Specific gravity, moisture content, cell turgor pressure, mechanical properties of tissue were determined. The cell section area, cell perimeter, and cell roundness and impact damage were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Bruised tissues exhibited the damage holes defined as areas occupied by crystal and increased intercellular regions. In the same manner, researchers used SEM to reveal the effect of the impact of energy on the tissue of fresh fruits such as pomegranate (Hussein et al, 2019), tomato (Sun et al, 2021), potato (Nikara et al, 2018), and kiwifruit (Gao et al, 2021). Hussein et al (2019) reported that although the damaged cells of the peel tissue were observable by SEM, the damage size could not be detectable between storage time (4 and 48 h).…”
Section: Surface Morphologymentioning
confidence: 99%
“…Bruised tissues exhibited the damage holes defined as areas occupied by crystal and increased intercellular regions. In the same manner, researchers used SEM to reveal the effect of the impact of energy on the tissue of fresh fruits such as pomegranate (Hussein et al, 2019), tomato (Sun et al, 2021), potato (Nikara et al, 2018), and kiwifruit (Gao et al, 2021). Hussein et al (2019) reported that although the damaged cells of the peel tissue were observable by SEM, the damage size could not be detectable between storage time (4 and 48 h).…”
Section: Surface Morphologymentioning
confidence: 99%
“…The impact acceleration of potato not only has a positive correlation with its damage (Thomson and Lopresti, 2018;Xie, 2020a), but also is the key parameter to the study of potato impact kinematics and dynamics. Researchers have adopted experimental studies 1 to analyze the potato mechanical impact and bruising based on various instruments including pendulum collision device, free drop collision device, electronic potato, instrumented sphere and acceleration measuring unit (Canneyt et al, 2004;Dănilă, 2015;Deng et al, 2020;Geyer et al, 2009;Hyde et al, 1992;Mathew and Hyde, 1997;Nikara et al, 2018;Rady and Soliman, 2015;Strehmel et al, 2010;Xie et al, 2018;Xie et al, 2020a;Xie et al, 2020b). But in the process of mechanized harvesting, sorting and transporting, potatoes usually collide with cylindrical steel rods with different tilt angles in different directions, which is a very complicated process.…”
Section: Introductionmentioning
confidence: 99%
“…Impact damage to potatoes is a common phenomenon during harvesting and post-harvesting operations. [1][2][3] It has been reported that 70% of the damage to potatoes is caused by harvesting, and impact and pressure are the main causes. [4] Mechanical damage and collision abrasion seriously affect potato yield and cause a dual decline of potato appearance and quality that affect the development of the entire potato industry.…”
Section: Introductionmentioning
confidence: 99%